Calcifying pseudoneoplasm of the neuraxis in direct continuity with a low‐grade glioma: A case report and review of the literature. Issue 5 (7th April 2017) - Higa, Nayuta; Yokoo, Hideaki; Hirano, Hirofumi; Yonezawa, Hajime; Oyoshi, Tatsuki; Goto, Yuko; Arita, Kazunori
Abstract : Calcifying pseudoneoplasms of the neuraxis (CAPNON) are presumed to be a non‐neoplastic reactive pathology, based on the frequent finding of granulomatous inflammation. To our knowledge, there are few reports of CAPNON in association with a neoplasm. Here, we report the case of a 62‐year‐old man presenting with headache, which was caused by CAPNON in the left cingulate gyrus. CT scan revealed a calcified mass exhibiting gradual growth and increasing peritumoral edema. MRI showed an intra‐axial hypointense mass on T1‐ and T2‐weighted images. Development of a peri‐lesional hyperintense lesion on T2‐weighted images suggested local edema or tumoral invasion. Gadolinium‐enhanced T1‐weighted images revealed mild peripheral enhancement of the calcified nodule. L‐methyl‐ 11 C methionine‐positron emission tomography revealed the uptake of tracer in the calcified nodule. The calcified mass and its enveloping brain tissue were removed using a parietal craniotomy. The calcified tissue was surrounded by spindle‐shaped cells positive for GFAP and nestin. The MIB‐1 labeling index of spindle cells was around 10% (i.e. a hot spot). Fourteen months after surgery, gadolinium‐enhanced MRI evidenced growth of a tiny residual lesion. Therefore, this report illustrates a potential case of CAPNON arising from low‐grade glial neoplasm.